The financial crash and maternity leave. Impact on parents and legislation - Eydal, Guðný Björk; Gíslason, Ingólfur V. (School of Social Sciences, 2023)
One of the effects of the bank crash that hit Iceland in 2008 was a severe cut in welfare spending. Parental leave was one of the spheres that were affected. In this article we will explain the origins and characteristics of the law on parental leave from 2000 and show how fathers and mothers used it. Then we discuss the changes that were made in the aftermath of the economic crisis, such as the cuts in economic compensation, and ask what effects this may have had on the uptake of parental leave and the situation of families with small children. This is based on data from the Parental Leave Fund on the one hand and, on the other hand, on the results from a survey among parents who had their first child in 2009. Finally, we discuss the changes in the laws on parental leave adopted by the Icelandic parliament in December 2012 where it was decided to extend in steps the individual rights of both parents to parental leave. Meðal afleiðinga bankahrunsins á Íslandi árið 2008 var verulegur niðurskurður á mörgum sviðum velferðarmála. Fæðingarorlof var einn þeirra þátta sem fékk að kenna á niðurskurðarhnífnum. Í þessari grein verður fjallað í stuttu máli um tilurð og einkenni laga um fæðingar og foreldraorlof frá árinu 2000, nýtingu orlofsins frá setningu laganna og til 2007 og hvað einkenndi hana. Þá er fjallað um breytingar sem gerðar voru í kjölfar efnahagskreppu, m.a. um niðurskurð á hámarki greiðslna, og spurt hvaða áhrif þær kunna að hafa haft á tilhögun fæðingarorlofs og hag barnafjölskyldna. Byggt er annars vegar á gögnum frá Fæðingarorlofssjóði og hins vegar niðurstöðum rannsóknar sem framkvæmd var sumarið 2012 meðal foreldra sem eignuðust sitt fyrsta barn árið 2009. Í lokakafla verður fjallað um þær breytingar sem Alþingi samþykkti í desember 2012 á lögum um fæðingarorlof þar sem ákveðið var að auka í áföngum rétt beggja foreldra til fæðingarorlofs.